Peran Kepemimpinan Perempuan dalam Pendidikan: Systematic Literature Review - Karim, Abdul; Febi Adriana Mutiara (NOKEN : Jurnal Pengelolaan Pendidikan, 2024)
Women are still underrepresented in leadership positions in most organizations. This study analyzes aspects of women's leadership, such as barriers, enablers, strengths, and weaknesses, to understand the challenges and opportunities they face. Using a systematic literature review method, the study included scholarly articles and books published between 2019 and 2024 from the Publish or Perish 8 application. The results show that research on women's leadership is mostly conducted in developed countries in fields such as social sciences, business, medicine, and education. In both developed and developing countries, women leaders face similar barriers, such as gender gaps, "glass ceiling" career barriers, organizational bias, lack of courage to be assertive, and limited professional networks. Several enabling factors can enhance women's leadership, such as mentoring programs, effective training, and an inclusive work culture. The strengths of women leaders include high emotional intelligence, empathy, democratic leadership style, and the ability to make decisions under pressure, which are very beneficial for organizations.